2012
DOI: 10.3758/s13414-012-0341-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sensory correspondences and cross talk between dimensions of connotative meaning: Visual angularity is hard, high-pitched, and bright

Abstract: Higher-pitched sounds are judged to be, among other things, sharper, harder, and brighter than lower-pitched sounds. Following Karwoski, Odbert, and Osgood (Journal of General Psychology 26:199-222, 1942), such cross-sensory correspondences are proposed to have a semantic basis, reflecting extensive bidirectional cross-activation among dimensions of connotative meaning. On this basis, the same core set of correspondences should emerge whichever sensory feature is used to probe it. More angular (sharper) shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 39 publications
8
87
0
Order By: Relevance
“…For instance, angular shapes are reliably matched to higher (rather than lower) auditory pitch (Marks, 1987;Walker, 2012). Congruence Specific to audition and taste, recent cognitive psychology and neuroscience research has demonstrated that people will reliably match specific (psycho-)acoustic and musical parameters with different tastes, flavors, and oral-somatosensory food-related experiences (Crisinel, et al, 2012;Crisinel & Spence, 2010a, 2010b, 2011, 2012a, 2012bMesz, Sigman, & Trevisan, 2012;Mesz, Trevisan, & Sigman, 2011;Simner, Cuskley, & Kirby, 2010).…”
Section: Crossmodal Correspondences Between Sound and Tastementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, angular shapes are reliably matched to higher (rather than lower) auditory pitch (Marks, 1987;Walker, 2012). Congruence Specific to audition and taste, recent cognitive psychology and neuroscience research has demonstrated that people will reliably match specific (psycho-)acoustic and musical parameters with different tastes, flavors, and oral-somatosensory food-related experiences (Crisinel, et al, 2012;Crisinel & Spence, 2010a, 2010b, 2011, 2012a, 2012bMesz, Sigman, & Trevisan, 2012;Mesz, Trevisan, & Sigman, 2011;Simner, Cuskley, & Kirby, 2010).…”
Section: Crossmodal Correspondences Between Sound and Tastementioning
confidence: 99%
“…According to one recent account, sound symbolism may be just a special case of the more general phenomenon of crossmodal correspondences (see Spence, 2011;Walker & Walker, 2012), which will be discussed in more detail in the next section.…”
Section: Sound Symbolism and Musical Meaningmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact connotative dimensions involved also require further elaboration. Much of Walker's work focuses a core set of connotations including: light/heavy, sharp/blunt, quick/slow, bright/dark, and small/large (e.g., P. Walker & Walker, 2012). Others have focused on connotations that comprise the three factors of connotative meaning discovered by Osgood, Suci, and Tannenbaum (1957), namely, evaluation (e.g., good/bad), potency (e.g., strong/ weak), and activity (e.g., active/passive; e.g., Miron, 1961;Tarte, 1982).…”
Section: Mechanisms For Associations Between Phonetic and Semantic Fementioning
confidence: 99%
“…Noteworthy, other studies have shown that the shape of a plate and food (when 94 it is round as compared to angular) can influence participants' sweetness ratings of the food 95 Here it is worth mentioning that, in spite of their perceptual basis, similarities across the 98 senses also surface in language (e.g., see the quote at the beginning of the Introduction, 99 Marks, 1978Marks, , 1996. With this in mind, we ask whether the potential hedonic-and intensity-100 related explanations/mediations of taste/shape correspondences may extend to taste words 101 and, if so, whether they reflect: a perceptual process; a common connotative meaning 102 (Walker, 2012 Dictionary, 'sharp' applied first to touch, then subsequently to taste (ca. 1000), visual shape 114 (1340), and hearing" (p. 190), indicating that shape-related words have been used to describe 115 tastes for several centuries, and thereby perhaps some kind of implicit relation between shape 116 and taste quality (see also Williams, 1976;Yu, 2003).…”
mentioning
confidence: 99%